2006
DOI: 10.1016/j.cardiores.2006.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hemodynamic overload of the atria is an important factor for gap junction remodeling in human and rat hearts

Abstract: Structural alteration of the atrial myocardium is an important factor in the disorganization of connexins and gap junction. Moreover, redistributed Cx43 do not form junction channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 42 publications
7
65
2
3
Order By: Relevance
“…Abnormal spatial distribution of connexins is a common observation during cardiopathies, heart failure, atrial fibrillation, and atrial dilation (8,107,168,295,334,362,389,402,438). In these clinical conditions, a fraction of connexins, notably connexin-43, is delocalized at the lateral membrane where they are scattered without ultrastructural evidence of junctional plaque formation.…”
Section: A Delocalization Of Connexinsmentioning
confidence: 99%
“…Abnormal spatial distribution of connexins is a common observation during cardiopathies, heart failure, atrial fibrillation, and atrial dilation (8,107,168,295,334,362,389,402,438). In these clinical conditions, a fraction of connexins, notably connexin-43, is delocalized at the lateral membrane where they are scattered without ultrastructural evidence of junctional plaque formation.…”
Section: A Delocalization Of Connexinsmentioning
confidence: 99%
“…Thus, two months after surgery, the infarcted rats had a left ventricular dysfunction and an enlarged and fibrotic left ventricle. It has been previously shown that regression of the heart remodelling in treated myocardial infracted rats was associated with re-phosphorylation and assembly of organized gap junction [11]. Thus, in the vehicle group, the large proportion of Cx43 was non-phosphorylated.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, in the vehicle group, the large proportion of Cx43 was non-phosphorylated. Because the phosphorylation sites regulate channel properties, assembly and targeting in junctional plaques [15], the dephosphorylated Cx43 from remodelling heart is responsible for depressed cellcell coupling [11]. Therefore, the reduction of a higher amount of non-phosphorylated Cx43 by OMACOR ® and the redistribution of Cx43 suggest a re-organisation of junctional areas in heart tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isoproterenol-induced hypertrophy provokes interstitial fibrosis (31,51), which can lead to discontinuities in propagating signals via gap junctions (56). Atrial function following isoproterenol-induced hypertrophy has been less well studied, although fibrosis and Cx40 gap junctional remodeling within the atria are symptomatic of hemodynamic overload and heart failure (22,53). The dramatic increase in atrial lacZ expression that was observed in response to isoproterenol administration may be indicative of a significant functional impairment of this tissue that could result from reduced signal propagation via Cx40 gap junctions, which triggers a transcriptional program whose readout is the lacZ transgenic reporter.…”
Section: Discussionmentioning
confidence: 99%